The joinder of claims according to the amendments of the law nro. 30293 - Franciskovic Ingunza, Beatriz A. (2021)
In this article we intend to outline some ideas to understand what is and what is the importance of procedural claim must refer to the law ofaction. The right ofaction becomes that faculty which has all legal subject, in its various manifestations, as designed, individual, collective person and unregistered organizations, of being brought before the court in search of effective judicial protection. Law which allows us, in case of a legal dispute or legal uncertainty, have recourse to a State organ for by the Judges who administer justice, we resolve such disputes.